Estudo de viabilidade técnica e econômica para o aproveitamento energético do biogás no município de entre rios do oeste Pr: produção centralizada versus produção descentralizada de biogás. - Lucio, Luís Thiago (2015)
The increase in population in recent decades has resulted in accelerated growth of food production demand. In this scenario, agricultural activity, especially swine, had to adapt to this new market reality through the production empowerment, developing new confinement techniques where the animal density per unit increases significantly. Consequently, this higher animals concentration per production unit confirms the intensification of organic contamination in the environment. However, the sanitary treatment of this residual biomass in anaerobic digestion systems enables the transformation of this environmental liability into an economic asset, once this treatment process enables the generation of two products with economic value - biogas and biofertilizers. Although this solution is environmentally feasible, from the economic point of view it is not always possible due to the costs of biomass treatment with energy purposes. Faced with this problem, an arrangement that demonstrates economically viable is the implementation of agricultural energy cooperatives, once this system allows scaling up the biogas production and enables the diversification of the use of this renewable energy source. In this context, this study aims, through a technical and economic feasibility analysis, identify the best scenario to implement agricultural cooperatives, focused on the residual biomass logistics and on the biogas transportation through pipelines. The methodology proposed in the work involving the municipality Entre Rios do Oeste (PR) has shown that the best scenario to produce biogas for energy purposes is the decentralized generation one, once the analyzed arrangements show a 9 years payback for electricity, 10 years for thermal energy and 7 years for vehicle biomethane, while in the biogas production centralized scenario the payback is 15 years for electricity, 10 years for vehicle biomethane, and there no payback for thermal energy arrangements. In addition, decentralized generation has lower operating costs and there is no legal restrictions on its operation. Keywords: Feasibility